2006
DOI: 10.1021/ja061036f
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Cleavage of RNA by a Metal-Free Artificial Nuclease Attached to Antisense Oligonucleotides

Abstract: RNA cleaving tris(2-aminobenzimidazoles) have been attached to DNA oligonucleotides via disulfide or amide bonds. The resulting conjugates are effective organocatalytic nucleases showing substrate and site selectivity as well as saturation kinetics. The benzimidazole conjugates also degrade enantiomeric RNA. This observation rules out contamination effects as an alternative explanation of RNA degradation. The pH dependency shows that the catalyst is most active in the deprotonated state. Typical half-lifes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 16 publications
4
63
0
1
Order By: Relevance
“…Over the last couple of decades, some progress has been achieved in the field of designing siteselective artificial ribonucleases [42][43][44][45][46][47][48][49][50][51][52][53][54]. It was shown that short peptides, containing either alternating leucine and arginine residues or imidazole-based catalytic groups, conjugated to antisense oligonucleotides targeting tRNA, were able to hydrolyze linkages adjacent to an oligonucleotide-binding site without involvement of exogenous species such as metal ions, enzymes or cofactors (e.g., RISC, RNase H) [42,44,45,47,50,51].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Over the last couple of decades, some progress has been achieved in the field of designing siteselective artificial ribonucleases [42][43][44][45][46][47][48][49][50][51][52][53][54]. It was shown that short peptides, containing either alternating leucine and arginine residues or imidazole-based catalytic groups, conjugated to antisense oligonucleotides targeting tRNA, were able to hydrolyze linkages adjacent to an oligonucleotide-binding site without involvement of exogenous species such as metal ions, enzymes or cofactors (e.g., RISC, RNase H) [42,44,45,47,50,51].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Reported results have shown that some small organic molecules, such as guanidine derivatives [15−17] , cyclodextrin derivatives [39,40] , macrocyclic polyamines [41] and peptides [42] , can cleave active phosphate diester and RNA. Göbel et al [43,44] put forward the concept of "metal free catalysis" and synthesized compounds 22a and 22b containing three guanidine side arms, which can catalyze RNA hydrolysis without metal ions. Furthermore, they attached 22b to DNA oligonucleotides by amide bonds to form artificial nucleases 23a and 23b containing both recognition group and catalytic hydrolytic group, which are named "metal-free nuclease" by the authors.…”
Section: Metal-free Catalysismentioning
confidence: 99%
“…Furthermore, they attached 22b to DNA oligonucleotides by amide bonds to form artificial nucleases 23a and 23b containing both recognition group and catalytic hydrolytic group, which are named "metal-free nuclease" by the authors. Compounds 23a and 23b have been successfully used to hydrolyze RNA sequence selectively [44] .…”
Section: Metal-free Catalysismentioning
confidence: 99%
“…Conjugation of various catalysts (other lanthanide(III) complexes, multi-nuclear metal complexes, or organic molecular scissors in Fig. (2) and (3) with DNA oligomers was also effective for site-selective RNA scission [24][25][26][27][28][29][30][31][32][33][34].…”
Section: Covalent Artificial Ribonucleasesmentioning
confidence: 99%